Organo‐Hydrogel Electrolytes with Versatile Environmental Adaptation for Advanced Flexible Aqueous Energy Storage Devices - Hongfei Wang; Muhammad Sohail Riaz; Tariq Ali; Jiawei Gu; Yijun Zhong; Yong Hu (Small Science, 2023)
With growing demands for portable electronics, flexible aqueous energy storage devices such as supercapacitors and Zn‐based batteries have drawn tremendous interest from both academic and industrial fields. Organo‐hydrogels, crosslinked amphiphilic polymers filled with organic solvents and water, are regarded as an ideal electrolyte candidate for portable electronic applications, especially due to their superior environmental adaptation. Organo‐hydrogels can reserve the advantages of the corresponding hydrogels and achieve some unique features such as broad temperature tolerance, high mechanical stability, strong interfacial interaction, and decent ionic conductivity. This review outlines the composition fundamentals, preparation methods, and comprehensive properties of reported organo‐hydrogel electrolytes. In particular, supercapacitors and Zn‐based batteries that operate under harsh temperature conditions and unusual mechanical deformations endowed by organo‐hydrogel electrolytes are further highlighted. Moreover, a unique perspective on the current challenges and future development directions of the organo‐hydrogel electrolytes for flexible energy storage is also provided.